Umrah pada Bulan Ramad?ân Adalah Haji; Studi Kualitas H?adîth dan Pemahamannya - Purwantoro Purwantoro (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2017)
Parable something with something else, we often see. Be it in the Qur’an or H?adîth of Prophet Muhammad saw. But what if the Prophet exemplifies or equate an act sunnah with deeds wajîb. In this respect there is a H?adîth of Prophet which states that Umrah in Ramad?ân is a Hajj. This article tries to to explore how the quality of H?adîth and how to understand it. So that we can practice the H?adîth correctly. This H?adîth needs to be understood correctly, Umrah is an act of sunnah can be equated with Hajj an act wajîb for Muslims.